BiFeO3 clad modified fiber optic gas sensor for room temperature applications. (2021) - Maricar, S. Mohamed Manjoor Shaib; Sastikumar, D.; Vanga, P. Reddy; Ashok, M.
Abstract: This communication reports multiferroic perovskite, nano crystallite BiFeO3 coated clad modified PMMA Fiber optic sensor functioning at room temperature and sensing Toxic gas in the environment. The porous BiFeO3 nanocrystalite clusters synthesized through solvothermal process and its structure, composition and morphology are analysed using XRD, EDAX and SEM. The crystallites were in agglomerated dimensions with pores up to 500 nm, average particle size 30 nm with rombohedral crystal structure. And it is used in the Fiber optic sensor modifying the original PMMA clad. Spectral response for BiFeO3 clad modified sensor is observed for Ammonia, Ethanol and Methanol, and the better sensitivity is found for Ammonia at room temperature compared to the other two vapours ethanol and Methanol.